Assessment of Industrially Produced Trans Fatty Acids in Traditional Dishes, Arabic Sweets, and Market Food Products and Its Risks on Non-communicable Diseases in Lebanon - Hoteit, Maha; Zoghbi, Edwina; Rady, Alissar; Shankiti, Iman; Ibrahim, Carla; Al-Jawaldeh, Ayoub (Frontiers in Nutrition, 2021)
Industrially-produced Trans fatty acids and partially hydrogenated fatty acids are a major dietary contributor to non-communicable diseases worldwide. To address the industrially produced Trans fatty acids food sources in Lebanon, a mapping exercise was enrolled between January 2019 and April 2021 to establish a national database. The 2019 survey was a pooled data from five separate sources and had relatively thirty types of traditional dishes. In contrast, the subsequent surveys in 2020 had a sample of thirty-five types of Arabic sweets and eighty types of Market food products. On the other hand, tThe 2021 survey covered of all types of butter , ghee and margarines available in the Lebanese markets. Our findings show that about 93% of the products tested in Lebanon, between 2019 and 2021, met the World Health Organization recommendations, while about 7% exceeded the limit. The mean level of the IP-TFAs Elaidic and Linolelaidic acid in most Traditional dishes (0.9%), Arabic sweets (0.6%), butter and margarines (1.6%), and market foods (0.52%) were relatively low compared with other countries. Despite the fact that trans fatty acids have a small impact on heart disease mortality in Lebanon, they are unquestionably significant. The persistence of food products with high quantities of trans fatty acids poses a health risk to Lebanese citizens. Fortunately, proper laws in Lebanon can easily remedy this situation.